Tracing the aqueduct of Koroni Castle in Messenia, southern Greece - Gerolymou , Konstantina; Panou , Basilis (Journal of Greek Archaeology, 2024)
Water management has been a focal point of recent studies dealing with ancient and medieval societies. In the rich in water resources region of Messenia the question of water management is now being investigated. However, the important large-scale infrastructures have not received sufficient attention. Aqueducts supplied water to the most prominent medieval castles of Messenia and/or their extra muros settlements (Niokastro, Koroni / Coron, Methoni / Modon, Kalamata and Androusa). The ruins of these aqueducts are more or less visible today. However, only the Ottoman aqueduct of Niokastro has been fully mapped and studied, while the other aqueducts are either partially published (Methoni, Kalamata) or not published at all (Androusa). It is important to explore and record these hydraulic infrastructures in order to protect them from further deterioration that might result from neglect, human activities (such as construction of buildings or roads) and the simple passage of time. This article presents the results of the investigations that were carried out in order to trace the route of the aqueduct of Koroni, provides an analysis of this significant building, and attempts to define the date of its construction and use.